Protean career development: exploring the individuals, organizational and job-related factors - Wong, Siew Chin; Mohd Rasdi, Roziah (Canadian Center of Science and Education, 2014)
Due to dynamics on both external and internal business environments, new forms of career management andcareer progression are increasingly being adopted at the individual level to maximize career success. Employeesare now more inclined to setup their own career agendas and establish benchmarks in measuring career successin a new trend as emphasized in protean career. Based on the SCCT and JCM models, the study provides atheoretical framework that examines the predictive potential of the individual, organizational and job-relatedfactors in explaining protean career among professional employees. The study is exploratory on the grounds ofliterature review. Professional employees may gain insights of the importance of protean career in careerdevelopment process. Practical interventions for HRD professionals are suggested to assist individuals andorganisations towards protean career management. Future research could provide a more holistic view of proteancareer and develop additional propositions.